Pelatihan Pemasaran Produk Sambal Kasia Berbasis Wisata Kuliner untuk Meningkatkan Perekonomian Lokal di Kampung Arar Kabupaten Sorong - Murni, Murni; Abubakar, Endang; Marshush, Ummi Hanifah; Ahmad Madaul, Rahful; Hilmansyah, Hilmi; Rian Histiariani, Aprisa; Widodo, Slamet; Desembardi, Faried; Tajuddin, Tamrin; Alam, Risma (Universitas Methodist Indonesia, 2024)
This Community Service program aims to enhance the competitiveness and added value of Kasia chili sauce, a flagship product of Kampung Arar. Kasia chili sauce is a distinctive product with significant potential to support the culinary tourism sector in the Kampung Arar area. However, a lack of effective marketing strategies has hindered the competitiveness of this product. Through this community service program, various activities are conducted to improve aspects of promotion, distribution, and packaging. Additionally, this initiative encourages collaboration with local culinary business owners to create a more integrated marketing ecosystem. The outcomes of this program are expected to increase the marketability of Kasia chili sauce, expand its market reach, and contribute to boosting the local community's income.